Finite element modelling on corrosion defects to determine the residual strength of offshore pipelines - Mohamed, Zulfaisal (2011)
Pipelines are assets of great importance in oil and gas industry and its failure contributes to safety, environment and economic implication. Further to that, operators reputation could be damaged if necessary actions never took place to secure the pipelines integrity. It is a very challenging task for operators or owners to maintain the integrity of pipelines for safe operation throughout design life period of 15 to 25 years. Corrosion is one of the main damage mechanisms that can cause pipelines to be in risk of failure. Field inspection is performed according to inspection schedule. The assessment is based on theoretical prediction model available in the industry. Two recommended practices; DNV RP-FI0l and ASME B31 G are widely used in determining the internal corrosion defect pressure capacity of pipelines. The proposed methodology is in line with the inspection data taken as a sample and has been analysed using probabilistic and empirical approach. The results determine whether the pipelines need to be repaired, replaced or can continue operating. However, these two methods could be insufficient to justify the integrity of pipelines. Thus, a high level assessment is proposed; finite element method is versatile and recommended to be used. The objectives of this study are to utilise finite element method, to carry out a comparison study of theoretical methods and establish validation criterion which is not well established currently. The results have shown that two theoretical methods have given significant results. The finite element method is the most appropriate solution to verify this method and further decision can be made to justify the residual strength of the pipelines. The validation part of finite element is a very crucial part to ensure the accuracy of the results. The validations were successfully done and can be proposed to be adopted as a basis in modelling corrosion defect. Finally, the results and findings are important for engineers to move to high level assessment of finite element method.